Concept analysis and development of international service - Valtteri Kaartemo (Taylor & Francis Group, 2018)
This article analyses and develops the concept of international service based on a review of 407 articles published in high-ranking international business and service research journals. The review confirms that usage of the key concept of international service is ambiguous, and a new definition is proposed, characterising international service as a value co-creation process between two or more resource-integrating actors that do not share influential institutional arrangements because of national borders. This new definition clarifies conceptual differences between international service, international activity and intercultural (cross-cultural) service, and between international product and service. The revised definition also highlights the existence of differences other than cultural variation and how differing institutional arrangements may in part be an effect of national borders. The study advances theory development in this research domain by providing a conceptually sound definition of international service, potentially eliminating some of the conceptual confusion that has until now posed challenges for the operationalisation of key concepts in the field. The new definition can also be expected to enhance collaboration between international business and service researchers.